PREVALENCE OF MALNUTRITION AND ASSOCIATED FACTORS AMONG CHILDREN UNDER-FIVE YEARS IN JUBA CITY - Kutjok, PHILIP; Nyicar, Simon D. (IJRDO-Journal of Applied Science, 2021)
ABSTRACT Introduction: Malnutrition still remains a major community health problem in developing countries. It is the most central risk factor for the burden of diseases. In South Sudan, child malnutrition rate is one of the most stern public health problem and the highest in the world. High malnutrition rates in the country pose a significant hindrance to achieving better child health outcomes. Objective: To evaluate prevalence of malnutrition and associated factors among children aged 6-59 months in Juba City, South Sudan Methods: A health facility based cross sectional study was conducted on 80 children aged 6-59 months from September 25, 2018 to October 18, 2018. Multistage sampling method was used to select children in health facilities. Children were selected from each health facility by simple random sampling. Anthropometric measurements and structured questions were used. Data were processed using EPi-info software and exported to SPSS for analysis. Then after, sex, age, height and weight transferred to ENA software to convert nutritional data into Z-scores of the indices; Height-for-age, weight-for-height and weight-for-age.  Results: The analysis of this study exposed that, 45.35%, 32.9% and 21.75% of children were underweight, wasted and stunted respectively. The prevalence of GAM and SAM in terms of z-scores and/or oedema and 95% confidence intervals were 92.4 % (84.4 - 96.5 95% C.I) and 74.7 % (64.1 - 83.0 95% C.I) respectively. The main associated factors of underweight, wasting and stunting were found to be child age, sex family occupation, marital status, parental education, monthly income, housing, poor family planning and early weaning practices among others. Delayed treatment of diarrhea, vomiting, coughing, and malaria in 6—59 months children were found related to prevalence of malnutrition. Conclusion: It’s determined that malnutrition still highly remains a principal problem among children aged 6-59 months.